Human Right to Access Public Information: The Experience of Ukraine and the Practice of the ECtHR - Shevchuk, Oleksandr Mykhailovych; Drozdov, OleÐºsandr Mykhailovych; Kozak, Vadim Anatoliyovych; Vyltsan, Anastasiia Oleksandrivna; Verhoglyad-Gerasymenko, Ðžlena Volodymyrivna (Faculty of Law, Hasanuddin University, 2023)
The guarantee of ensuring the right to access public information is an important condition and criterion for functioning in a legal democratic state. In addition, realizing the right to access public information is essential for preventing and detecting corruption. The purpose of this work is to analyze international legal rules and standards, as well as to provide some examples of the practice of the European Court of Human Rights in the context of the implementation of the right to access public information. It has been established that the right to access public information is a component of the human right to information and is a fundamental constitutional human right. The existing practice of the European Court of Human Rights confirms the importance of protecting the right of access to public information. It indicates to states that it is mandatory to comply with it, the expediency of applying an effective system of control measures to implement the right under study. The paper analyzes theoretical and legal approaches to understanding the human right to access public information and determines its place in human rights. An analysis of the practice of the European Court of Human Rights regarding the right to access public information made it possible to identify existing shortcomings in the legislation of the Member States and Ukraine and to find ways and methods for solving such problems and prospects for preventing such violations in the future, as well as the possibility of applying the decisions of the European Court of Human Rights to improve the current domestic legislation in this area.